Metode Layanan Bimbingan Dan Konseling Untuk Membangun Kompetensi Difabel Netra - Dhian Riskiana Putri; Puji Prihwanto (STKIP Andi Matappa, 2021)
This study aims to find the formulation of a counseling and guidance service strategy for the visually impaired. People with visual impairments experience problems in the form of loss or reduced function of the sense of sight that hinders their daily activities. The condition with visual impairments creates a feeling of insecurity and has difficulty interacting with other people. This situation is exacerbated by the perception of society that people with visual impairments are unable to do work like other people in general, and only become a burden to their family and other people around them. Therefore, assistance is needed in the form of guidance and counseling services to help develop self-confidence for people with visual impairments, as well as foster their ability to do daily work. This research uses the library research method (library research), which is research that obtains data from library sources, such as books, newspapers, documents, journal articles, and internet media. This study resulted in the formulation of guidance and counseling programs offered for blind people with disabilities, including (1) physical and mental guidance, including religious guidance, sports, mobility orientation, and daily activities; (2) Social guidance, including Braille reading and writing, language and arithmetic; (3) Guidance on business / work skills, including handicrafts, massage and the arts. The counseling technique that is appropriate for the blind diffable is the reality therapy technique.